2014
DOI: 10.1037/neu0000004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory deficits in illicit polydrug users are associated with the average long-term typical dose of ecstasy typically consumed in a single session.

Abstract: Prospective memory deficits in illicit polydrug users are associated with the average long term typical dose of ecstasy typically consumed in a single session. AbstractRationale Neuroimaging evidence suggests that ecstasy-related reductions in SERT densities relate more closely to the number of tablets typically consumed per session rather than estimated total lifetime use. In order to better understand the basis of drug related deficits in prospective memory (PM) we explored the association between PM and ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Gallagher and colleagues argued that the number of tablets used is a better predictor than the estimated total lifetime use. They showed that the typical ecstasy dose consumed in a single session is an important predictor of prospective memory impairments with higher doses giving rise to greater impairment [ 52 ]. However, when knowing the amount of tablets taken, the exact dose of MDMA is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Gallagher and colleagues argued that the number of tablets used is a better predictor than the estimated total lifetime use. They showed that the typical ecstasy dose consumed in a single session is an important predictor of prospective memory impairments with higher doses giving rise to greater impairment [ 52 ]. However, when knowing the amount of tablets taken, the exact dose of MDMA is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen distinct tasks were used to assess prospective memory across the included studies (Table 1). These were the Cambridge Prospective Memory Test (CAMPROMPT; Wilson et al 2005), Video-Based Prospective Memory Task (V-B PMT; Titov and Knight 2001), Memory for Intentions Screening Test (MIST; Raskin et al 2010), belonging subtest of the Rivermead Behavioural Memory Test (RBMT; Wilson et al 1985), Six Elements Test (SET; Kliegel et al 2007), Designated Crosses Test (DC; Bedi and Redman 2008b), Virtual Week (VW; Rendell and Craik 2000), Fruit Test (FT; Cuttler et al 2012), Pattern Test (Hadjiefthyvoulou et al 2010), Pattern Recognition Prospective Memory Task (PRPMT; Gallagher et al 2014), Fatigue Time-Based Prospective Memory Test (FTBPT; Gallagher et al 2014), Computerised Shopping Task (CDT; Laloyaux et al 2012), Short-Interval Prospective Memory Task (SIPMT; McHale and Hunt 2008), Jansari-Agnew-Akesson-Murphy Task (JAAMT; Jansari et al 2014) and Prospective Remembering Video Procedure (PRVP; Seed et al 2005). Ratings of ‘established psychometric properties’ were based on previously reported psychometric properties of the tasks (see S4) using a 1–3 scale (1 = measures with acceptable test-retest reliability and concurrent validity; 2 = concurrent validity (objective measures) and questionable or no evidence of test-retest reliability or split-half reliability, and 3 = no evidence of reliability and where concurrent validity was based on self-report measures).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple testing correction controlling the False Discovery Rate (FDR) was applied in these correlations ( Benjamini and Yekutieli, 2001 ). The FDR was set to 0.10, which implies that the proportion of significant associations which are actually false discoveries is limited no >10%, as in other neuropsychological studies ( Gallagher et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%